METABOLIC DIVERSITY OF ZOANTHARIANS COLLECTED AT BRAZILIAN OCEANIC ISLANDS - Bianca Del B. Sahm; Ana C. Zanatta; Francisco da Chagas L. Pinto; Otília D. L. Pessoa; Diego V. Wilke; Paula C. Jimenez; Norberto P. Lopes; Tito M. C. Lotufo; Letícia V. Costa-Lotufo (Química Nova)
Zoantharians are benthic marine organisms widespread in Brazilian tropical shallow waters. Recent evidence suggests that the metabolism of these cnidarians may be influenced by diverse environmental factors. We have previously shown that two species of Palythoa found on the Brazilian coast share metabolomic similarities related to their location. Herein, through gas chromatography coupled with mass spectrometry (GC-MS) and liquid chromatography tandem mass spectrometry (LC-MS/MS) analysis, along with molecular networking, we assessed polar and apolar extracts from 28 samples of Palythoa spp. and Zoanthus spp. collected at different Brazilian oceanic islands - Saint Peter and Saint Paul Archipelago, Fernando de Noronha Archipelago, Rocas Atoll and Trindade Island - to describe and compare their metabolome in such isolated regions, under reduced interference of anthropic actions. The chemical profiles of zoantharians from Brazilian oceanic islands include fatty acids and sterol derivatives, in apolar fractions, and ecdysteroids, phospholipids, ceramides, mycosporine-like amino acids, and alkaloids in polar fractions. These chemical classes are similar to those described for the continental zoanthids, previously assessed. The results presented herein reveal a preserved metabolome across the analyzed species, Palythoa caribaeorum, Palythoa variabilis and Zoanthus spp., and between island and continental organisms, suggesting core species-specific metabolites and a portion of an environmentally-driven chemical expression.